A Bibliometric and Scoping Review of Research Integrity among Research Scholars - Das, Jateendra; Rout, Sarat Kumar; Sardar, Bikshyatsib; Sahoo, Pranayini; Mahapatra, Soumyabrata; Dash, Shubhashree (Asian Journal of Interdisciplinary Research, 2025)
This article describes the scoping that was grounded on Arksey and O’Malley's (2005) mode of operation, and follows the PRISMA extension for scoping reviews. The scoping review aimed to explore a global perspective on research integrity among research scholars, given how little we know about the knowledge, attitudes, and practices of research academics around research integrity. The researchers completed a systematic search for articles spanning 368 records published from 2014 - 2023 from Science Direct, EBSCO and ProQuest. Ultimately, 37 empirical studies were included after screening and a critical appraisal. The co-authorship network illustrated distinct small, but meaningful clusters with limited institutional connections among researchers in the field, while the keywords analysis revealed dominant themes of research misconduct, research integrity, and knowledge, revealing gaps in areas such as questionable research practices and informed consent. Additionally, despite illustrating a great deal of variation, research integrity is generally overlapping, along discipline and across regions, growing with relative higher rates of questionable research practices, including academic authorship, selective reporting, and p-hacking, while as before, at least related, and hardly even acknowledged, of being involved in Fabrication, Falsification and Plagiarism (FFP). Yes, notably, barriers towards protecting research integrity manifest as publication pressures, and institutional support is horrendous. A positive association was given for publication among researchers, at least apparently correlated, and provided with respect to researchers with misconduct. Scholarly education about ethics and institutional support may vary widely, which suggests a range of variables for focus on and moreover blanket customized training and institutional restructuring supporting research integrity.